2016
DOI: 10.1186/s12974-016-0508-8
|View full text |Cite
|
Sign up to set email alerts
|

CD200R1 agonist attenuates glial activation, inflammatory reactions, and hypersensitivity immediately after its intrathecal application in a rat neuropathic pain model

Abstract: BackgroundInteraction of CD200 with its receptor CD200R has an immunoregulatory role and attenuates various types of neuroinflammatory diseases.MethodsImmunofluorescence staining, western blot analysis, and RT-PCR were used to investigate the modulatory effects of CD200 fusion protein (CD200Fc) on activation of microglia and astrocytes as well as synthesis of pro- (TNF, IL-1β, IL-6) and anti-inflammatory (IL-4, IL-10) cytokines in the L4–L5 spinal cord segments in relation to behavioral signs of neuropathic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 74 publications
1
40
3
2
Order By: Relevance
“…We thus further explored the glial localization of CXCL10 in the spinal cord through double immunofluorescence staining. The enlarged area and strength of the immunostaining determined through the image analysis corresponded well with the sites showing activated microglia and astrocytes after injury [17,18]. As previously described, spinal glial activation can be determined by measuring Iba-1 (microglia) and GFAP (astrocytes) immunoreactivity [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus further explored the glial localization of CXCL10 in the spinal cord through double immunofluorescence staining. The enlarged area and strength of the immunostaining determined through the image analysis corresponded well with the sites showing activated microglia and astrocytes after injury [17,18]. As previously described, spinal glial activation can be determined by measuring Iba-1 (microglia) and GFAP (astrocytes) immunoreactivity [14].…”
Section: Discussionmentioning
confidence: 99%
“…Because glial cells are the main effectors and regulators of the spinal cord, activated populations of glial cells could produce a wide variety of proinflammatory cytokines that strongly affect the pathogenesis of sensory hypersensitivity [6,8,17,22]. Among these cytokines, TNF-α and IL-6 are known to function as potent proinflammatory cytokines during the reperfusion period [6,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that microglia activation and subsequent proinflammatory cytokine expression are responsible for enhanced pain hypersensitivity [32], we used Iba-1 as the microglial activation marker to see whether PF played a role in the activation of spinal microglia in the CFA-induced inflammatory pain mice. It was found that the fluorescence intensity in the spinal cord dorsal horn of CFA-injected mice was increased by more than 50% compared with that in Sham group, and the expression of Iba-1 was reduced after PF treatment (Fig.…”
Section: Pf Inhibits Microglial Activation After Cfa Injectionmentioning
confidence: 99%
“…Существуют иммунологические механизмы развития ПНБ, которые запускаются воспалительной реакцией и активаци-ей глиальных клеток в соответствующих сегментах спинно-го мозга [31,32].…”
unclassified
“…Экспериментальные исследования показали, что инт-ратекальное введение крысам CD200R1 вызывает у них бы-строе ослабление глиальной активации и синтеза провоспа-лительных цитокинов спинного мозга, что приводит к уменьшению невропатической боли после эксперименталь-ного повреждения нерва [31].…”
unclassified